Using image series as media in narrative text writing skills in 5 level of elementary school - Julia, Cheri; Indihadi, Dian; Suryana, Yusuf (Universitas Riau Kepulauan, 2023)
Writing is the starting point of a lesson that continues on to the next lesson. Writing skills are said to be high-level skills that must be trained through various writing exercises and then expressed in written language, such as in narrative texts. In the activity of writing narrative texts, the difficulties experienced by students were due to not being used to writing essays. Therefore, the problems above need to be overcome so as to increase students' interest in making narrative texts. The solution developed by the researcher is through the use of serial picture media, so that students can develop skills in writing narrative text covering aspects of content, structure, and language. The purpose of this research in general is to describe the results of writing narrative texts from the use of picture series media made by students of class V SD. This study uses a context-based descriptive analysis research method using a qualitative approach. This is because the data obtained will be examined and analysed as it is by described it in words. Based on the results of the study, some of the fifth grade students at SDN 1 Cikukulu were already able to compose narrative texts through the use of serial picture media seen from the results of their writing. Based on the results of the first assignment and the results of the second assignment there was an increase from an average of 6.3 to 8.15 which was obtained from the results of the students' writing.